2019
DOI: 10.3892/etm.2019.7214
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin improves heart preservation through inhibiting hypoxia‑dependent L‑type calcium channels in cardiomyocytes

Abstract: The current study aimed to evaluate whether luteolin could improve long-term heart preservation; this was achieved by evaluating the heart following long-term storage in University of Wisconsin solution (the control group) and in solutions containing three luteolin concentrations. The effects of different preservation methods were evaluated with respect to cardiac function while hearts were in custom-made ex vivo Langendorff perfusion systems. Different preservation methods were evaluated with respect to the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Li et al (2019) suggest that LUT protects heart tissues in STZinduced diabetic mice by modulating Nrf2-mediated oxidative stress and NF-κB-mediated inflammatory responses. In another study, Yan et al (2019) demonstrated LUT's protective effects during long-term heart preservation in a dose-dependent manner, which may be accomplished by inhibiting hypoxia-dependent L-type calcium channels. Yao et al (2016) also showed Luteolin-7-O-Glucoside cardioprotective effects by inhibiting the DOXinduced intracellular level of ROS and apoptosis, potentially acting as a therapeutic agent Figure 1 The experimental scheme and the effects of LUT on body weight and heart weight in DOX induced-cardiotoxicity model rats.…”
Section: Introductionmentioning
confidence: 95%
“…Li et al (2019) suggest that LUT protects heart tissues in STZinduced diabetic mice by modulating Nrf2-mediated oxidative stress and NF-κB-mediated inflammatory responses. In another study, Yan et al (2019) demonstrated LUT's protective effects during long-term heart preservation in a dose-dependent manner, which may be accomplished by inhibiting hypoxia-dependent L-type calcium channels. Yao et al (2016) also showed Luteolin-7-O-Glucoside cardioprotective effects by inhibiting the DOXinduced intracellular level of ROS and apoptosis, potentially acting as a therapeutic agent Figure 1 The experimental scheme and the effects of LUT on body weight and heart weight in DOX induced-cardiotoxicity model rats.…”
Section: Introductionmentioning
confidence: 95%
“…Luteolin prevented bone loss in postmenopausal OP by reducing the differentiation ability of osteoclasts [95]. Also, luteolin inhibited L-type calcium currents in ventricular myocytes under hypoxia conditions and ameliorated calcium ion overload in rat cardiomyocytes [96]. By analyzing EXD targets, we hypothesize that EXD acts synergistically to mediate OP via calcium regulation and apoptosis, e.g., several studies have shown that ESR1 variants are related to postmenopausal OP [97][98][99], and ESR1 gene polymorphisms may be predictive of OP in female patients with Crohn's disease [65].…”
Section: Discussionmentioning
confidence: 92%
“…Luteolin prevented bone loss in postmenopausal OP by reducing the differentiation ability of osteoclasts [ 95 ]. Also, luteolin inhibited L-type calcium currents in ventricular myocytes under hypoxia conditions and ameliorated calcium ion overload in rat cardiomyocytes [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Madhesh andVaiyapuri (2005 and found that luteolin (0.3 mg/kg/day) could protect cardiac function and prevent myocardial infarction by reducing mitochondrial lipid peroxidation (a route that produce ROS in vivo) and increasing the mitochondrial antioxidant levels as shown in isoproterenol induced myocardial infarction model in rats (Manju et al, 2005;Madhesh and Vaiyapuri, 2012). Luteolin appears to be an inhibitor of L-type calcium channels as confirmed by Yan et al (2018), Yan et al (2019). Luteolin (7.5, 15, or 30 μM) ameliorated calcium overload in freshly isolated cardiomyocytes, accompanied by suppressed Protein Kinase A (PKA) activity and enhanced Ca 2+ -Mg 2+ -ATPase activity (Yan et al, 2018).…”
Section: Natural Flavones Exhibit Potential In Treating Hf Via Dual Regulation Of Calcium and Rosmentioning
confidence: 90%